Five-Factor Modified Frailty Index as a Predictor of Complications Following Total Ankle Arthroplasty. Issue 1 (January 2022) - Lewis, Lauren; Jupiter, Daniel; Panchbhavi, Vinod K.; Chen, Jie
Category: Ankle Arthritis; Ankle; Other Introduction/Purpose: Ankle arthritis can significantly diminish the function and quality of life of affected individuals. Treatment options for end-stage ankle arthritis include total ankle arthroplasty (TAA). Ongoing research seeks to identify patient factors associated with a higher risk of post-operative complications following TAA. A 5-item modified frailty index (mFI-5) has been found to predict adverse outcomes of multiple orthopaedic procedures. The aim of this study was to evaluate the suitability of the mFI-5 as a risk stratification tool for patients undergoing TAA. Methods: A retrospective review of the National Surgical Quality Improvement Program (NSQIP) database was performed on patients undergoing TAA between the years of 2011 and 2017. Data on patient demographics, post-operative complications, and length of stay were collected. Bivariate analysis and multivariate logistic regression were subsequently performed to investigate frailty as a possible predictor of post-operative complications. Results: 1035 patients were identified (mean age = 63.9 years). Complication rates significantly increased with increasing mFI-5 score, from 5.24% in patients with no mFI-5 variables to 19.38% in patients with two or more mFI-5 variables present (P <0.0001). When comparing patients with an mFI-5 score of 0 to patients with an mFI-5 score of 2, 30-day readmission rate increased from 0.24% to 3.1% (P> 0.017), length of stay increased from 1.79 days to 2.18 days (P >0.007), adverse discharge rate increased from 3.81% to 15.5% (P <0.0001), and wound complications increased from 0.24% to 1.55% (> 0.02). After controlling for demographic factors, length of stay, and operative time, mFI-5 score remained significantly associated with patients' risk of developing any complication and 30-day readmission rate. Conclusion: Frailty as defined by the mFI-5 is associated with adverse outcomes following TAA. Implementing the mFI-5 as a risk stratification tool may assist in identifying patients who are at an elevated risk of sustaining a complication, and may allow for improved informed decision-making and perioperative care when considering TAA.